2013
DOI: 10.1093/jxb/ert122
|View full text |Cite
|
Sign up to set email alerts
|

Growth and nodulation of symbiotic Medicago truncatula at different levels of phosphorus availability

Abstract: Medicago truncatula is an important model plant for characterization of P deficiency on leguminous plants at the physiological and molecular levels. Growth optimization of this plant with regard to P supply is the first essential step for elucidation of the role of P in regulation of nodulation. Hence, a study was carried out to address the growth pattern of M. truncatula hydroponically grown at different gradual increases in P levels. The findings revealed that M. truncatula had a narrow P regime, with an opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
77
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(88 citation statements)
references
References 48 publications
3
77
1
1
Order By: Relevance
“…S3, S4, and S5 and Datasets S2-S4). These data support the premise that legume nodules subjected to low Pi are not sucrose-limited (13,28). Instead of the initial cleaving of sucrose with the aid of ATPdependent AI, McCP-31-induced nodules subjected to low Pi significantly activated the energy-saving SS/UDP-GPP pathway that remained unaffected in MmSWRI9-induced nodules (Fig.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…S3, S4, and S5 and Datasets S2-S4). These data support the premise that legume nodules subjected to low Pi are not sucrose-limited (13,28). Instead of the initial cleaving of sucrose with the aid of ATPdependent AI, McCP-31-induced nodules subjected to low Pi significantly activated the energy-saving SS/UDP-GPP pathway that remained unaffected in MmSWRI9-induced nodules (Fig.…”
Section: Discussionsupporting
confidence: 83%
“…S3 and Dataset S2). Several studies have reported that down-regulation of SNF capacity is associated with the accumulation of asparagine in nodules of Pi-stressed plants (28,39). These reports further strengthen the premise that asparagine accumulation plays a role in N feedback regulation of SNF capacity in MmSWRI9-inoculated plants.…”
Section: Discussionsupporting
confidence: 71%
“…PHO2-like is annotated as encoding an E2 ubiquitin conjugating enzyme, and its Arabidopsis (Arabidopsis thaliana) ortholog (35% amino acid identity, E value = 4e-104) is involved in phosphorous accumulation (Park et al, 2014). Not only can phosphorous availability affect nodulation and N 2 fixation (Graham and Rosas, 1979;Jakobsen, 1985;Graham, 1992;Sulieman, 2013) but in Arabidopsis, AtPHO2 ortholog interacts directly with the E3 product of Nitrogen Limitation Adaption, which mediates plant responses to N limitation (Park et al, 2014). Moreover, E2 ubiquitin conjugate enzymes are presumed to interact with multiple E3 partners that could lead to the proteolytic degradation of a larger range of uncharacterized substrates (Smalle and Vierstra, 2004).…”
Section: Genetics Of Nodulationmentioning
confidence: 99%
“…Most studies on the effect of P limitation on N 2 -fixation have largely been confined to model legumes such as Lupinus albus (Schulze et al, 2006, Thuynsma et al, 2013 and Medicago truncatula (Tang et al, 2001, Sulieman et al, 2013. Despite the high legume diversity found on the P-poor soils of the CFR (Goldblatt and Manning 2002), little is known about the functional mechanisms which affect N nutrition within the nodules of indigenous legumes.…”
Section: Introductionmentioning
confidence: 99%